Applying the Nernst Equation to Control ORP in Denitrification Process for Uranium-Containing Nuclear Effluent with High Loads of Nitrogen and COD - Venturini, M. (2022)
Fil: Venturini, M. Ministerio de Economía. Secretaría de Energía. Comisión Nacional de Energía Atómica. Laboratorio de Biominería y Biotecnología Ambiental; Argentina.